Microcomedones in non‐lesional acne prone skin New orientations on comedogenesis and its prevention. (3rd October 2019) - Fontao, F.; von Engelbrechten, M.; Seilaz, C.; Sorg, O.; Saurat, J.H.
Abstract: Background: In non‐lesional skin of acne patients, cyanoacrylate skin surface stripping can harvest a structure called microcomedone (MC) which is the earliest phase of comedogenesis; the root of any subsequent clinical lesion and a target for the prevention of acne relapses. More information is needed on the putative biochemical contributors (biomarkers) of comedogenesis expressed in MC. Methods: Proteins expressed in MC were screened by proteomics, immunohistochemistry and Western blotting. The in vitro effects of a comedolytic Silybum marianum fruit extract (SMFE) were studied in sebocyte cultures by RNA‐Seq and modulation of CYP1A1 by qPCR and enzymatic activity. MC severity was correlated to lesions counts and keratin expression during 48 weeks in 23 acne patients using a topical comedolytic formulation containing SMFE. Results: Two infundibular keratins, K75 and K79, co‐localized in MC with the sebocyte progenitor cell marker LRIG1 and were used as a biomarker of comedogenesis for the follow‐up of patients. In cultured sebocytes exposed to SMFE (i) transcriptomic analysis showed an up‐regulation by a factor of 15 of RNA coding for K75 and (ii) the gene expression and catalytic activity of CYP1A1 under exposure to dioxin was decreased. In the acne patients using SMFE, the MC index in non‐lesional skin decreased over time and remained until the 48th week, significantly lower than that of the first week. There was a high correlation between the decrease of MC index and the decrease and stability of the clinical lesions counts over time. Importantly, a low MC index status was found to be associated with a significant higher K75 expression in microcomedones. Discussion: These observations provide new orientations on the mechanism of comedogenesis and its prevention. Maintaining a low MC status in non‐lesional skin is a sound target for the prevention of acne relapse and a good sentinel of acne remissions.